Chronic colonization of rat airways with Pseudomonas aeruginosa. - Boyd, R L (1983)
Colonization of the airways of rats by Pseudomonas aeruginosa was established by treating the animals with hexamethylphosphoramide (HMPA) and inoculating with P. aeruginosa. Male Sprague-Dawley rats were given tap water (controls) or HMPA in the drinking water at 2 or 4 mg/ml. The ciliated cells of the airway epithelium were denuded, and microulcerative lesions in the epithelium were induced in the HMPA-treated rats. After 2 weeks of treatment, the rats were inoculated by transoral intratracheal instillation with 5 X 10(7) CFU of P. aeruginosa obtained from a cystic fibrosis patient. Two weeks after inoculation, P. aeruginosa was cultured from the airways, and scanning and transmission electron microscopy showed bacilli adhering to or invading the injured airway epithelium. P. aeruginosa was present in tracheal and intrapulmonary tissue homogenates of 9% of the P. aeruginosa-inoculated control rats (n = 22) as compared with 61% of the 2-mg/ml (n = 18) and 65% of the 4-mg/ml (n = 20) HMPA-treated rats (P less than 0.05). No dose-response relationship was found between 2 and 4 mg of HMPA per ml and colonization. Contamination of 47% of all of the rats with Mycoplasma pulmonis, as indicated by a positive enzyme-linked immunosorbent assay for immunoglobulin G, had no discernible significant effect on colonization by P. aeruginosa. These results indicate that colonization of the rat airway by P. aeruginosa can be achieved experimentally by treating the animals with HMPA. This research supports the hypothesis that colonization by P. aeruginosa may occur in airways where the ciliated epithelium has been injured and epithelial lesions exist.